Artisanal fishing, dolphins, and interactive pinger: A study from a passive acoustic perspective. Issue 8 (14th May 2021) - Buscaino, Giuseppa; Ceraulo, Maria; Alonge, Giuseppe; Pace, Daniela Silvia; Grammauta, Rosario; Maccarrone, Vincenzo; Bonanno, Angelo; Mazzola, Salvatore; Papale, Elena
Abstract: Dolphins interact with many types of fishing gear, causing damage to fishing activities and in some cases facing harm and becoming entangled as bycatch. In this study, the behaviour of bottlenose dolphins during their interaction with set nets, equipped with and without interactive pingers, was investigated. Acoustic monitoring of the nets was conducted for a total of 56 hauls and 814.9 hr of recordings, from the 16 October to 13 November 2015, along the coast of Lampedusa island (Sicilian Channel, Italy, Mediterranean Sea). The level of interaction between dolphins and the nets was evaluated considering the number of dolphin clicks grouped over time (single acoustic incursion on each net), the duration of every acoustic incursion, and the number of dolphin clicks per incursion. Moreover, the catch rate was measured as the number of fish per hour for each net. Based on the recording time of dolphin clicks, the spatio‐temporal development of the interaction with the nets located in different bays of the island was assessed. The duration of the interaction between dolphins and nets significantly increased over the study period, with a concomitant reduction in catch rate. The interactive pinger showed efficacy in protecting the nets from dolphin depredation during the first period of 36 hauls and 11 fishing days (higher catch rates and lower incursion durations), whereas no differences were found in any interaction parameters between pinger and control nets in the second period (20 hauls and six fishing days). Interactive pingers may be an effective, short‐term (2–3 weeks) tool in deterring depredation by bottlenose dolphins in small‐scale artisanal fisheries. Other mitigation approaches, such as gear modification, lessons learned through outreach, and passive acoustic monitoring of the nets, could improve the management of the interactions between fisheries and bottlenose dolphins.